THE LEARNING CREATIVITY PROFILE THROUGH AUDIO PODCAST MEDIA AS AUDITORY LEARNING STYLE IN SD ISLAM KREATIF - Mifa Maulida Arfianingsih; Syadeli Hanafi; Lukman Nulhakim (JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
Abstract The purpose of this research is to determine the profile of students' learning creativity in thematic learning of the Indonesian Language Subject in the 4th grade at SD Islam Kreatif. The method used is the descriptive method. The sample in this research is the 4th grade students of SD Islam Kreatif with a total of 19 students. The research instrument used is a questionnaire to measure the learning creativity. The creativity indicators are curiosity, imaginative, feeling of challenged, dared to take risks, and respect. Students' learning creativity through the use of podcast-based audio media has a creative profile. Students have learning creativity and show a positive response of 32% with very creative criteria and 68% with creative criteriaKeywords : Creativity; Podcasts; Auditory Learning Style